2012
DOI: 10.1038/bjc.2012.184
|View full text |Cite
|
Sign up to set email alerts
|

Value of DCE-MRI and FDG-PET/CT in the prediction of response to preoperative chemotherapy with bevacizumab for colorectal liver metastases

Abstract: Background:The purpose of this study was to assess the role of dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) and 18F-fluorodeoxyglucose positron emission tomography computed tomography (FDG-PET/CT) for evaluation of response to chemotherapy and bevacizumab and for prediction of progression-free survival (PFS) in patients with metastatic colorectal cancer (mCRC) with potentially resectable liver lesions.Methods:A total of 19 mCRC patients were treated with FOLFOX/FOLFIRI and bevacizumab followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(80 citation statements)
references
References 46 publications
6
72
1
1
Order By: Relevance
“…A high baseline K trans has been shown to correlate with better outcome with cytotoxic agents in CRC (52). In a study by De Bruyne et al (53), a decrease in K trans of more than 40% after bevacizumab-containing chemotherapy was associated with better progression-free survival, although this has not been corroborated in other studies. DW imaging can also help detect small lesions (<10 mm) that are not detectable with other modalities (54).…”
Section: Role Of Imaging In Systemic Chemotherapymentioning
confidence: 89%
“…A high baseline K trans has been shown to correlate with better outcome with cytotoxic agents in CRC (52). In a study by De Bruyne et al (53), a decrease in K trans of more than 40% after bevacizumab-containing chemotherapy was associated with better progression-free survival, although this has not been corroborated in other studies. DW imaging can also help detect small lesions (<10 mm) that are not detectable with other modalities (54).…”
Section: Role Of Imaging In Systemic Chemotherapymentioning
confidence: 89%
“…For example, in 4 studies of primary rectal cancer and mCRC treated with bevacizumab and cytotoxic therapy, pretreatment and early acute pharmacodynamic changes in tumor F, K trans , and BV did not relate to extent of tumor regression or RECIST response (62)(63)(64)(65). This finding could be interpreted as proof that imaging biomarkers do not relate to outcome in this setting.…”
Section: Role Of Measuring Tumor Heterogeneitymentioning
confidence: 98%
“…De Bruyne et al [127] 19 DCE-MRI AUC decrease CRC metastases Bevacizumab Vriens et al [129] 23 DCE-MRI K trans decrease CRC metastases Cytotoxic therapy Coenegrachts et al [130] 10 DCE-MRI Kep increase CRC metastases Bevacizumab + FOLFIRI Deckers et al [126] 20 DWI ADC decrease CRC metastases Chemotherapy Niwa et al [133] 63 DWI ADC decrease PDAC Gemcitabine Cuneo et al [134] 12 DWI ADC increase PDAC Chemoradiation Yao et al [135] 39 pCT BF decrease PanNET Bevacizumab ± everolimus Miyazaki et al [132] [115,116] .…”
Section: Primary Liver Tumorsmentioning
confidence: 99%
“…Many studies have been conducted with DCE-MRI, probably as a consequence of the standardization of DCE-MRI-derived endpoints. De Bruyne et al [127] reported that bevacizumab therapy could decrease DCE-MRI-derived AUC in patients with CRC liver metastases. Vriens et al [128] reported a large reduction in DCE-MRI-derived perfusion parameters and glucose metabolic rate at 18 F-FDG PET/CT in CRC metastases treated with bevacizumab.…”
Section: Liver Metastasesmentioning
confidence: 99%